Polymorphisms in the Mitochondrial Genome Are Associated With Bullous Pemphigoid in Germans - Russlies, Juliane; Fähnrich, Anke; Witte, Mareike; Yin, Junping; Benoit, Sandrine; Gläser, Regine; Günter, Claudia; Eming, Rüdiger; Erdmann, Jeanette; Gola, Damian; Gupta, Yask; Holtsche, Maike Marleen; et al. (Frontiers in Immunology, 2019)
Bullous pemphigoid (BP) is the most prevalent autoimmune skin blistering disease and is characterized by the generation of autoantibodies against the hemidesmosomal proteins BP180 (type XVII collagen) and BP230. Most intriguingly, BP is distinct from other autoimmune diseases because it predominantly affects elderly individuals above the age of 75 years, raising the question why autoantibodies and the clinical lesions of BP emerges mostly in this later stage of life, even in individuals harboring known putative BP-associated germline gene variants. The mitochondrial genome (mtDNA) is a potential candidate to provide additional insights into the BP etiology; however, the mtDNA has not been extensively explored to date. Therefore, we sequenced the whole mtDNA of German BP patients (n=180) and age- and sex-matched healthy controls (n=188) using next generation sequencing (NGS) technology, followed by the replication study using Sanger sequencing of an additional independent BP (n=89) and control cohort (n=104). While the BP and control groups showed comparable mitochondrial haplogroup distributions, the haplogroup T exhibited a tendency of higher frequency in BP patients suffering from neurodegenerative diseases (ND) compared to BP patients without ND (p= 0.1448, Fisher’s exact test). A total of four single nucleotide polymorphisms (SNPs) in the mtDNA, namely, m.16263T>C, m.11914G>A, m.16051A>G, and m.16162A>G, were found to be significantly associated with BP based on the meta-analysis of our NGS data and the Sanger sequencing data (p=0.0017, p=0.0132, p=0.0129, and p=0.0076, respectively, Peto’s test). In summary, our study is the first to interrogate the whole mtDNA in BP patients and controls and to implicate multiple novel mtDNA variants in disease susceptibility. Studies using larger cohorts and more diverse populations are warranted to explore the functional consequences of the mtDNA variants identified in this study on immune and skin cells to understand their contributions to BP pathology.